2001
DOI: 10.4319/lo.2001.46.3.0557
|View full text |Cite
|
Sign up to set email alerts
|

Unusual bacterioplankton community structure in ultra‐oligotrophic Crater Lake

Abstract: The bacterioplankton assemblage in Crater Lake, Oregon (U.S.A.), is different from communities found in other oxygenated lakes, as demonstrated by four small subunit ribosomal ribonucleic acid (SSU rRNA) gene clone libraries and oligonucleotide probe hybridization to RNA from lake water. Populations in the euphotic zone of this deep (589 m), oligotrophic caldera lake are dominated by two phylogenetic clusters of currently uncultivated bacteria: CL120-10, a newly identified cluster in the verrucomicrobiales, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
245
2
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(261 citation statements)
references
References 44 publications
11
245
2
3
Order By: Relevance
“…The coexistence of different bacterial genotypes belonging to the same species-like phylogenetic group is well documented for marine (1,18,19,35,45) and freshwater habitats (8,9,10,11,27,30,43). Recently, Acinas et al (1) demonstrated by the construction and analysis of 16S rRNA clone libraries that a coastal bacterioplankton community contained a very high diversity of ribotypes, the vast majority of which fell into phylogenetically microdiverse sequence clusters (Ͻ1% divergent 16S rRNA sequences).…”
mentioning
confidence: 99%
“…The coexistence of different bacterial genotypes belonging to the same species-like phylogenetic group is well documented for marine (1,18,19,35,45) and freshwater habitats (8,9,10,11,27,30,43). Recently, Acinas et al (1) demonstrated by the construction and analysis of 16S rRNA clone libraries that a coastal bacterioplankton community contained a very high diversity of ribotypes, the vast majority of which fell into phylogenetically microdiverse sequence clusters (Ͻ1% divergent 16S rRNA sequences).…”
mentioning
confidence: 99%
“…The comparison cannot be extended to hypolimnion as no information is provided on the hypolimetic bacterioplankton of Lake Constance. A decrease of prokaryotic cell abundance was found in other deep lakes such as Lake Baikal [36], Crater Lake [14], Lake Tanganyika [34]. Nevertheless, as far as we know, long-term (decades) data on prokaryote abundance along the water column of deep lakes have not yet been published.…”
Section: Discussionmentioning
confidence: 99%
“…Among other factors affecting microbial diversity, depth gradient resulted in various marine systems to be a modulator of relative abundance of Bacteria and Archaea [11][12][13]. So far, few data have been published on distinguishing between Bacteria and Archaea in the hypolimnion of deep lakes with the exception of the high altitude ultraoligotrophic Crater Lake, USA [14,15] and the subalpine Lake Maggiore, Italy [16]. In Crater Lake the Group I marine Crenarchaeota accounted for 16-27% of deep-water populations, showing a similarity between ocean microbial populations and those living in an ultraoligotrophic deep lake [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the 341F/1492R primer pair amplification was: 95 1C for 5 min followed by 35 cycles of 95 1C for 1 min, 50 1C for 1 min and 72 1C for 2.5 min, and a final cycle of 72 1C for 10 min. Archaeal amplification was tested with Arch25F (Urbach et al, 2001) paired with U1492R. Amplified DNA was checked for quality by agarose gel electrophoresis, bands were gel purified using the Qiaquick Gel Extraction Kit (Qiagen, Valencia, CA, USA), and cloned into the vector pCR4-TOPO using the TOPO TA Cloning Kit (Invitrogen, CA, USA) following the manufacturer's instructions.…”
Section: Dna Extraction Pcr Amplification Alignment and Phylogenetimentioning
confidence: 99%